Bidirectional Energy Transfer in Bi‐Tm‐Codoped Glasses. (27th January 2014) - Li, Yang; Ma, Zhijun; Sharafudeen, Kaniyarakkal; Dong, Guoping; Qiu, Jianrong
<x xml:space="preserve">Abstract</x> In this manuscript, we report an ultrabroadband luminescence covering the whole 1000–1800 nm in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sxkpg7n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Binm+</alternatives> singly doping glass, and a superbroadband emission from 1000 to 2000 nm in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sxkpgb9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Binm+</alternatives>‐Tm3+‐codoped glasses excited at 808, 980 nm, respectively. We also confirm a bidirectional energy transfer mechanism between <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sxkpgcv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Binm+</alternatives> and Tm3+. Broadband luminescence is used to realize 1–2 μm optical amplifier and tunable laser. Luminescent properties of glasses are investigated systematically. Peak position and intensity of the near‐infrared emission depend strongly on excitation wavelength. Based on a collaborative investigation of the photoluminescence and luminescence decay, a plausible bidirectional energy transfer mechanism between <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sxkpg86" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Binm+</alternatives> and Tm3+ is confirmed.